Analysis Of Wakaf Bank Financing Model for Empowerment Based on Islamic Microfinance an Islamic Economic Perspective - Syarif, Ahmad Hazas; Ramadhana, Amelia Tika; Suharto, Suharto (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: The formulation of the problem in this study is how the waqf bank financing model is Empowering Based on Islamic Micro Finance at Islamic Micro Waqf Banks at the Minhadlul Ulum Islamic Boarding School Lampung. Methodology: In this study, using qualitative research. The population in this study were employees and customers at the Minhad'lul Ulum Micro Waqf Bank Lampung. The sampling technique used is a purposive sampling technique with criteria determined by the researcher, namely customers who have micro businesses and want to make their businesses more productive. Findings: Waqf Bank itself uses a Sharia-based financing system in its financing mechanism for its customers using the Qardh contract and joint responsibility system, where joint responsibility is the responsibility of each customer in one group or individually, where if one customer is in one group If the person cannot pay the installments, then the other members in the group are the ones who are responsible for paying the installments, either one person who pays or it is paid jointly or jointly. In this Qardh contract, in essence, it is a form of help and affection for the borrower, not a means to seek profit for the lender, in which there is no reward and excess return. From the financing provided by BWM, customers can increase their business and get maximum results from their usual income, therefore financing from the Micro Waqf Bank is very helpful for customers, especially the poor, middle and lower classes.